Stratigraphic lithic assemblages from shell middens on the northern coast of Santa Cruz (Patagonia, Argentina) - Hammond, Heidi (2015)
Results of the study of artifact lithic assemblages recovered from systematic excavations of shell middens on the northern coast of Santa Cruz (Patagonia Argentina), are presented. The characteristics and composition of lithic assemblages are analyzed to discuss functionality and integrity of the archaeological sites, and also to evaluate general trends of the technological organization of human groups that inhabited the area. This work represents an initial approach to the interpretation of the archaeological record of coastal shell middens from the study of lithic artifact assemblages recovered in stratigraphic contexts.The evidence from the artifact assemblages allows discussion of the activities that hunter gatherers carried out on shell middens, as well as issues of technological organization of manufacture of stone artifacts and the strategies related to exploitation of lithic raw materials in the study area. Coastal shell middens are places were multiple activities were performed. Regarding lithic technology, the manufacture and maintenance of stone tools, the use thereof, and the discarding of tools and debitage are the activities most represented.